Relación subjetiva-objetiva en el desarrollo del pensamiento matemático de objetos reales a objetos matemáticos en la educación, didáctica de las operaciones matemáticas - Juan David Romero Serna (Logos Ciencia & Tecnología, 2014)
In the development of mathematical thinking necessary to establish relationships that allow the teacher and the student generate observations on the medium that lead to the reading of the context, from the concepts that have been established through culturally mathematics education, that enable subject-object relationship in a symbiosis such a transformation that generates actions and enables the development of this research on mathematical operations from the shares of construction, deconstruction occurs and since the number of roots of mathematical objects potentially perfect.